A Review on Sustainable Practices in Scientific Research (Global Journal of Science Frontier Research, 2024)
Many sustainable practices to reduce footprints in scientific research have been described Plenty were proven to reduce environmental impacts while not affecting data quality However many scientists struggle with initiating change due to a lack in sustainability orientated education A thorough understanding of sustainable practices is urgently needed to enable efficient and safe implementation Therefore the focus of this review is to provide a comprehensive collection and discussion of practices in chemical biochemical biologic and medical laboratories Amongst others strategies to reduce plastic waste lessen energy consumption reducing footprints when handling equipment and optimizing protocols or procurement will be included To enable scientists in different circumstances to benefit from this review both simple low effort steps and actions at larger scale will be discussed Similarly this review will address opportunities for bottom-up approaches by individual scientists and top-down approaches that require entire groups or institutions to participate Additionally benefits of sustainable practice such reduced expenses increased safety and optimized workflows are described because of their importance to motivate and justify change In essence this review should raise awareness by compiling the plethora of sustainable practices available Furthermore it should empower researchers with the knowledge and tools to incorporate sustainable practices whether they are driven by passion regulation or workflow optimization